Sedimentary architecture and depositional environment of Kudat Formation, Sabah, Malaysia - Ghaheri, S. (Institute of Physics Publishing, 2018)
Kudat Formation originated from deep marine environment. Three lithofacies association of deep marine turbidity channel was discovered in three Members of the Kudat Formation in Kudat Peninsula, Sabah, Malaysia. Turbidite and deep marine architecture elements was described based on detailed sedimentological studies. Four architecture elements were identified based on each facies association and their lithology properties and character: inner external levee that was formed by turbidity flows spill out from their confinement of channel belt; Lobes sheet that was formed during downslope debris flows associated with levee; Channel fill which sediments deposited from high to low density currents with different value of sediment concentration; and overbank terrace which was formed by rapid suspension sedimentation. The depositional environment of Kudat Formation is shelf to deep marine fan. Â© Published under licence by IOP Publishing Ltd.